PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH OPEN ENDED DAN TINGKAT KECEMASAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMPN 1 MENGWI - Dewi, Ni Luh Sintya (LPPM Universitas Bina Bangsa, 2025)
Mathematics learning is a teaching and learning process built by teachers to develop students' creative thinking, and can improve the ability to construct new knowledge as an effort to improve good mastery of mathematics material. However, it is still difficult for a student to understand mathematics lessons and many still use lecture methods that tend to be oriented towards the material listed in the book. There needs to be innovation in the application of learning models that also affect the level of anxiety and the desired results. One of them is the Open Ended Problem-Based learning model including a learning approach that involves students in solving open problems that can increase student creativity, improve students' mathematical thinking patterns, improve students' talents and interests in mathematics, and help students think critically. The objectives of this study are: (1) To determine whether there is a difference in mathematics learning outcomes between students who follow the Open Ended Problem-Based learning model and students who follow the conventional learning model. (2) To determine whether there is a difference in mathematics learning outcomes of students who have high levels of anxiety with students who have low levels of anxiety. (3) To determine whether there is an interaction effect between the Open Ended Problem-Based learning model and anxiety levels on mathematics learning outcomes. Hypothesis test results using two-way ANOVA. Based on the results of the research and data analysis, it was obtained that (1) There is a significant influence on mathematics learning outcomes between the group of students who follow the Open Ended Problem Based learning model and the group of students who follow the conventional learning model. (2) There is no significant influence on students' mathematics learning outcomes between students who have high anxiety and the group of students who have low anxiety. (3) There is a significant interaction between the Open Ended Problem Based learning model and the level of anxiety on students' mathematics learning outcomes.